Deep Classroom Management Management Improving Student Learning Achievement In School - Yuniar, A. Firah; Nurazikin, Nurazikin; Irmawati, Irmawati; Indoese, Indoese; Nismalasari, Andi (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2024)
AR RAHMAN KAJU MTS School is one of the educational institutions at the junior high school level which is currently trying to create quality education for all people and restore students' right to learn. Among the efforts carried out to achieve these goals are facilitating cheap and quality education and the implementation of education that favors the needs of the surrounding environment and the students themselves, this is based on the participation of all components of MTS AR RAHMAN KAJU who aspire to create independent learning citizens and useful. From this background, the problems faced are how to implement class-based management carried out at MTS AR RAHMAN KAJU School and how to make student-based management work well. Therefore, this institution is interesting to study with the aim of knowing the implementation of management that is applied, is it in accordance with the concept of class-based management and how to condition management that is completely left to students can be a point more than management at other educational institutions that only focus on teachers. This type of research includes field research. The approach in this study is a qualitative descriptive approach. In collecting data the author uses the method of observation, interviews, and documentation. In analyzing the data, a comparative descriptive method was used, namely making generalizations based on facts and subsequent events. The results of the analysis were compared with scientific concepts that became the standard approach in this research. The results of this study are that the MTS AR RAHMAN KAJU School is an educational institution that carries out management implementation that is oriented to inculcating awareness, is flexible, according to student needs and restores students' right to learn